1998
DOI: 10.1089/mdr.1998.4.65
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolution of Rifampicin Resistance inStreptococcus pneumoniae

Abstract: Rifampicin resistance has arisen in several different species of bacteria because of alterations to one or more regions in the target of the antibiotic, the beta-subunit of RNA polymerase encoded by rpoB. Nucleotide sequence analysis of a 270 bp fragment of rpoB from 16 clinical rifampicin-susceptible isolates of Streptococcus pneumoniae, 8 clinical rifampicin-resistant isolates, and 3 spontaneous rifampicin-resistant mutants, has revealed that, as with previously examined species, point mutations within the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 28 publications
3
38
0
Order By: Relevance
“…The determination of the DNA changes which arise in independent Rif r mutants should reveal the mutator specificity of the strain 800T51. Searching the pneumococcal genome sequence (with the TIGR database) indicates that cluster I is almost identical in pneumococcus and other bacteria, as confirmed recently by Enright et al (9). A 1,500-bp segment including cluster I was amplified in independent Rif r mutants.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…The determination of the DNA changes which arise in independent Rif r mutants should reveal the mutator specificity of the strain 800T51. Searching the pneumococcal genome sequence (with the TIGR database) indicates that cluster I is almost identical in pneumococcus and other bacteria, as confirmed recently by Enright et al (9). A 1,500-bp segment including cluster I was amplified in independent Rif r mutants.…”
Section: Resultssupporting
confidence: 54%
“…Out of 23 independent Rif r mutants, the mutations were found on three codons of cluster I, among which was the codon for serine 495 (Table 5). Rif r mutations in this codon were previously reported in E. coli but not in S. pneumoniae (9,19). We have detected GC-to-TA (and CG-to-AT) transversions in three types of Rif r mutants out of five types characterized.…”
mentioning
confidence: 54%
“…Among the rifampin-resistant donors, we noted His526 substitutions, also known to confer resistance in Bacillus, Mycobacterium, and Escherichia (8,30). We identified Asp526 (S. pneumoniae Pn16, S. intermedius) and Tyr526 (Streptococcus oralis, S. pneumoniae strain R6, S. pneumoniae strain 96129) substitutions.…”
Section: Methodsmentioning
confidence: 93%
“…It has been reported that rifampicin resistance could be acquired due to an RNA polymerase single point mutation. 34,35) These two strains may be candidates for selected rifampicin-resistant mutants. The isolates of B. animalis subsp.…”
Section: Discussionmentioning
confidence: 99%